Effects of selenium-enriched bacterial protein supplementation on egg quality, antioxidant profiles, and gene expression in laying hens - Muhammad, Ibrahim Aliyu (2021)
Micronutrients are paramount in animal nutrition for the normal biological, and physiological process of the living cells. Selenium (Se), known to play a vital role in human and animal biochemical functions. Se bioavailability depends on the form of dietary Se offered. Organic forms have been recognized to have superior absorption and efficacy compared to inorganic forms. Researchers are now developing an interest in exploring different forms of organic Se using strains of microorganisms, capable of biotransforming inorganic Se to elemental Se and accumulate in their cells as Se-containing proteins. The use of Se-enriched bacterial proteins as ‘dietary Se supplements’ in animal nutrition would provide sufficient organic Se for humans and animals in the food chain, potentially addressing selenium deficiency. Thus, the current research is centered on investigating such an advantage and how it can successfully be transferred to the end product while reaping its benefits. In the first experiment of this study, there was an optimization of culture medium and temperature for the production of organic selenium by the Stenotrophomonas maltophilia (ADS18) isolated from hot spring water. The results showed brain heart infusion supports higher cell biomass at 35 0C for an incubation time lesser than 48 h. The higher value of pellets totals Se yield was 45.10, 30.20, and 27.48 for nutrient broth, brain heart infusion, and tryptic soy media, respectively. However, after adding the same amount of Na2SeO3 to all tested media, organic Se of S. maltophilia was readily concentrated in both supernatant and cell biomass, with higher yields of cell biomass in brain heart media and organic Se nutrient broth media. In the second experiment, the effects of sodium selenite, selenium yeast, and Stenotrophomonas maltophilia enriched bacterial protein (ADS18) on laying performance, egg quality traits, egg yolk, and tissue Se concentrations, and small intestine morphology under a normal environment was examined. A total of 144 Lohman Brown-Classic laying hens, 18 weeks of age were randomly divided into four equal groups, each contained six replicates. A corn-soybean meal basal diet was supplemented with no Se supplementation (Con), basal diet plus 0.3 mg/kg feed inorganic sodium selenite (Na2SeO3) (SS), basal diet plus 0.3 mg/kg Se-yeast (SY), and basal diet plus 0.3 mg/kg Stenotrophomonas maltophilia ADS18 enriched bacterial protein. The results showed that different dietary Se sources affected laying rate, average egg weight, daily egg mass, FCR, live body weight (LBW) significantly (p < 0.05). However, average daily feed intake and shell-less and broken egg were unaffected (p > 0.05) among the treatment groups. Furthermore, the dietary Se supplemented group had higher (p < 0.05) Se concentrations in egg yolk and breast tissue compared to the control group. Hens fed ADS18 or Se-Yeast groups had significantly (p < 0.05) higher villi height in the duodenum and jejunum than those fed Na2SeO3 or a basal diet for the small intestine morphology. However, as compared to organic Se fed (ADS18 or Se-Yeast) hens, the basal diet group had the highest (p < 0.05) ileum villus height, while the SS group had the lowest among the treatment groups. In comparison to the Con group, dietary Se treatment decreased total serum cholesterol and serum triglycerides levels significantly (p < 0.05). Specifically, organic Se (Se-enriched bacteria and Se-yeast) sources show better results in some performance index, intestinal villus height, some serum biochemical parameters compared to the inorganic form (sodium selenite). The third experiment examined the effect of sodium selenite, selenium yeast, and bacterial enriched protein on egg yolk and tissue antioxidant profiles and oxidative stability. The egg yolk and breast tissue samples were used for the analysis of antioxidant profile (total carotene, cholesterol, phenolic, and flavonoid content), oxidative stabilityinfluencing status (antioxidant capacity, thiobarbituric acid reactive substances (TBARS)), and egg yolk color assay. Fresh eggs were sampled on the 16 weeks and stored at 4 ± 2 0C for 14 days for shelf-life determinations and subjected to the same analysis. The results showed that dietary Se supplementation significantly (p < 0.05) improved egg yolk color, the antioxidant profile of egg yolk, and breast meat (total carotenoid and phenol content). The oxidative stability parameters of the eggs, breast and thigh muscle, and plasma showed significantly (p < 0.05) decreased concentrations of primary oxidation products (MDA) formed in the egg yolk, tissue, and blood collected. However, the MDA content increased (p < 0.05) with an advanced storage period in Con and Na2SeO3 supplemented groups. Moreover, as compared to Na2SeO3-fed hen eggs, dietary organic Se (ADS18 or Se-Yeast) had the lowest MDA content after two weeks of storage. The source of organic Se supplemented is important for egg enrichment and antioxidant properties. Thus, possible to produce fortified eggs enriched with organic selenium. The fourth experiment investigates the effects of organic and inorganic dietary selenium supplementation on gene expression profiles in oviduct tissue, antioxidant enzyme capacity, and the caecum microbiome of laying hens. A total of 24 hens were selected randomly from the four treatments and slaughter at 39 weeks old, and 16-weeks of the experiment. Uteri and liver tissue samples were collected from hens for quantitative polymerase chain reaction (qPCR). The hens ceacum digesta was collected for microbial population quantification. The basal diets supplemented with 0.3 mg/kg of different organic Se sources and sodium selenite improves the hen’s caecum microbiota, upregulated uterine genes, and selenoproteins mRNA levels. This research reaps the advantage of tissue sampling from specialized segments of the oviduct that consecutively form different egg components. Both organic Se (bacterial Se proteins and Se-yeast) sources improve the expression of functional genes involved in the egg (eggshell biomineralization) formation and selenoproteins compared to inorganic and non-Se supplemented hens. In conclusion, different dietary Se sources can improve the biological activities of the layers; however, Se from organic sources appears to be reliable and may be used to produce Se-enriched animal products. Eggs seem to be a valuable source of Se for humans, as the Se is distinctively incorporated into chemical compounds, and consequently, plays a vital role. Indeed, this will provide consumers with a range of animal-derived products that have been nutritionally enriched in a way that they can act as a vector for providing significant quantities of health-promoting nutrients to help achieve and maintain good health.